Analysis of Affecting Factors in Increasing the Quality of Performance of Employees at Health - Rini Sulistyoasih; Yuly Peristiowati; Indasah Indasah (Jurnal Keperawatan, 2023)
Performance is a result of work both in quality and quantity achieved by an employee in carrying out his duties. The purpose of this study is to analyzethe influence effect of motivation, reinforcement and job satisfaction on the quality of employee performance at the Gresik District Health Center, Gresik Regency.The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe influence effect of motivation, reinforcement and job satisfaction on the quality of employee performance at the Gresik District Health Center, Gresik Regency. The total population of 171 respondents and a sample of 120 respondents were taken using the Simple Random Sampling technique. The findings showed that almost half of the respondents havegood category motivation as many as 57 respondents (48%). Almost half of the respondentshave a good category of reinforcement as many as 59 respondents (49%). Almost half of the respondents have job satisfaction in the moderately satisfied category as many as 51 respondents (43%). Most respondentshave quality performance in the good category as many as 61 respondents (51%). Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that simultaneously there is the effect of motivation, reinforcement and job satisfaction on the quality of employee performance at the Gresik District Health Center, Gresik Regency with an effect of 74.9%.